Meningkatkan Kompetensi Guru dalam Penyusunan RPP yang Baik dan Benar Melalui Pendampingan Berbasis KKG di SDN Model Mataram - Yatmini, Yatmini (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
Background study of this research was target teachers’ competency at SD Negeri Model Mataram in arranging proper lesson plan was low so it has impact less confidence in learning process. The solusion was conducted guidance either group or individual in arranging proper and good lesson plan. It aimed to know effectiveness of implementing guidance based|MGMP in effort improving teachers’ competency in arranging proper and good lesson plan, which useful to improve professionalism as headmaster and for teachers to improve learning process in classroom. Action hypothesis: it improved target teachers’ competency at SDN Negeri Model Mataram first semester in acedemic year 2015/2016 in arranging good and proper lesson plan. This research was conducted in two cycles, every cycle was twoo meetings. Stage in every cycle was planning, acting, observing, and reflecting. Indicator of succesful in this research was; 1) result of headmasters’ observation or teachers’ observation as long as guidance process got mean score > 4,0, 2) result of teachers’ work in arranging lesson plan was> 100% with mean score > 70,00. Result of reseach in cycle I mean score of headmasters’ observation (3,30), mean score of teachers’ observation (3,40) and mean score of individual work result (66,40) with percentage of completeness (10%). In cycle II mean score of headmasters’ observation (4,30), mean score of teachers’ observation (4,20), and mean score of individual work result (82,40)with percentage of completeness (100%). Indicator of successful was reached, this research was succeed and stopped in cycle II. Conclusion; implementing guidance could improve target teachers’ competency at SD Negeri Model Mataram in arranging good and proper lesson plan. Suggested in order to others headmaster conducted similar research in effort improving teachers’ competency , and for teacher in order to be able arrange good and proper lesson plan.